Applying Traditional Non-Contractual Civil Liability Rules to Holding Company’s Responsibility for Subsidiary Acts - Ibrahim Abdipour; Boshra Karimi (آموزه‌‌های فقه مدني, 2020)
Holding Group and its subsidiary, one of the most active in the economic community today, despite the lack of special provisions in the Iranian legal system have been operating in the Iranian economic system for some time. Therefore, in order to deduce the laws and laws governing their relations, we have to refer to the existing rules and general laws. One of the issues with this group cooperation which is afflicted is the liability or non-liability of the Holding Company against the Subsidiary’s creditors is due to the holding and management of the Holding Company in each of the Subsidiaries and their independent legal personality. After disputing views on the unity or multiplicity of legal entities between this group of companies and, as a result, of Holding Company’s absolute responsibility or non-responsibility, we chose a third intermediate opinion on the relative independence of Holding Company against its subsidiaries. After examining the arguments of the supporters of the theory of relative independence in Western law, such as the doctrine of corporate legal personality hijab, fraud against the law, prohibition of abuse of power, according to the legalization of the Iranian legal system based on the Islamic legal system To jurisprudential rules such as Harmless, arrogance, everyone has a benefit; it has a disadvantage, cause and... and as well as related legal articles, the choice of causation rule, and rectifying of non-contractual civil liability-based article of the provisions of the statutory non-contractual civil liability, such as Articles 1, 7, 11, 12 of the Civil Liability Act as a general criterion in the holding and basis of the liability of the holding company against the actions of subsidiaries, seems justified.